2015
DOI: 10.1038/nsmb.3096
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based energetics of protein interfaces guides foot-and-mouth disease virus vaccine design

Abstract: Summary Virus capsids are primed for disassembly yet capsid integrity is key to generating a protective immune response. Here we devise a computational method to assess relative stability of protein-protein interfaces and use it to design improved candidate vaccines for two of the least stable, but globally important, serotypes of Foot-and-Mouth Disease virus (FMDV), O and SAT2. FMDV capsids comprise identical pentameric protein subunits held together by tenuous non-covalent interactions, and are often unstabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(125 citation statements)
references
References 54 publications
3
120
2
Order By: Relevance
“…Indeed these regions can be targeted to overstabilize the virus capsid, for example by capsid engineering for improved vaccines (23), or to destabilize the capsid: for example, NAb E18 binds here and causes ejection of the genome from enterovirus EV71 (13). We have found that the potent NAb R10 Fab binds in this region and somewhat destabilizes the particles, consistent with HAV uncoating also proceeding via changes at the pentamer interface.…”
Section: Discussionmentioning
confidence: 63%
“…Indeed these regions can be targeted to overstabilize the virus capsid, for example by capsid engineering for improved vaccines (23), or to destabilize the capsid: for example, NAb E18 binds here and causes ejection of the genome from enterovirus EV71 (13). We have found that the potent NAb R10 Fab binds in this region and somewhat destabilizes the particles, consistent with HAV uncoating also proceeding via changes at the pentamer interface.…”
Section: Discussionmentioning
confidence: 63%
“…We recently showed that using reverse genetic approaches, we could improve stability by introducing stabilising mutations into a SAT2 infectious clone and recovering stabilised viruses [20]. Residue substitutions were predicted by comparing crystallography structures, sequence data, in silico calculations and modelling of the inter-pentameric interfaces between the thermostable A serotype and the more unstable O and SAT2 serotype viruses [20].…”
Section: Introductionmentioning
confidence: 99%
“…Recent the manipulation of the biological properties of field or laboratory strains [17][18][19] and structural analyses of the capsid have allowed for the design of thermostable mutations [20,21] integrated into reverse genetic approaches [22,23]. Several studies have shown that chimeric vaccines successfully induce protective immune responses and protect FMD host species against live virus challenge [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Deciphering the molecular basis that define capsid stability is important not only for the understanding of acid-induced uncoating but also for the improvement of aphthovirus vaccines based on empty capsids or inactivated virions (14)(15)(16)(17)(18). Along this line, the analysis of picornavirus mutants with altered acid sensitivities has provided valuable information to understand the mechanism of acid-dependent uncoating and to understand the molecular basis of capsid stability (13,(19)(20)(21)(22)(23)(24)(25).…”
Section: Importancementioning
confidence: 98%